Core-Level Spectroscopy with Hard and Soft X‑rays on Phosphorus-Containing Compounds for Energy Conversion and Storage - Wibowo, Romualdus Enggar; Garcia-Diez, Raul; van der Merwe, Marianne; Duarte-Ruiz, Daniel; Ha, Yang; Félix, Roberto; Efimenko, Anna; Bystron, Tomas; Prokop, Martin; Wilks, Regan G.; Bouzek, Karel; Yang, Wanli; et al. (Journal of Physical Chemistry C, 2023)
The electronic properties of nine solid phosphorus (P)containing compounds with varying oxidation states and chemical environments, including GaP(‑III), InP(‑III), red-P(0), H3P(III)O3, Na2H2P2(IV)O6, H3P(V)O4, KH2P(V)O4, Na2HP(V)O4, and InP(V)O4, are investigated using X-ray absorption near-edge structure (XANES) spectroscopy in the hard (P K-edge) and soft X-ray regime (P L2,3edge). We find shifts in the absorption-edge positions and correlate them with the ligands surrounding the P atom, likely causing a different core−hole interaction screening for different compounds. Complementing the experimental analysis, ab initio many-body calculations of XANES spectra provide insights into the excitonic nature of the observed spectral features and their impact on the electronic structure of the materials. Furthermore, we report on P K-edge XANES measurements on aqueous phosphorus-containing acids, including H3PO3, H3PO4, and their mixtures. At first sight, the spectra of the aqueous acids are similar to those of their solid counterparts. However, close inspection reveals a slight red shift of the absorption edge and the presence of fewer spectral features compared with spectra of the respective solids. Mixtures of aqueous acids display spectral features corresponding to the individual components, indicating the potential for speciation and quantification through fingerprinting (Figure Presented).
CRIS-Team Scopus Importer:2023-12-15